BIOCHEMICAL STUDY OF CERTAIN ENZYMES IN DENGUE FEVER PATIENTS - SUMAN, JAIN; KUMAR, SAMAR RAJENDRAR; SONAL, SOGANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the present study is to correlate the effect of certain enzymes in diagnosis of dengue fever (DF) and impact of these elevated/decreased blood levels of enzymes on patients of DF. Methods: The study was carried out on 30 patients suspected to be suffering from DF. Blood sample was collected and tested for various parameters such as protein (albumin), lactate dehydrogenase (LDH), creatinine kinase (CK), C-reactive protein (CRP), acid phosphatase, alkaline phosphatase, serum glutamic oxaloacetic transaminase (SGOT), and serum glutamic pyruvic transaminase (SGPT). Results: Serum enzymes such as LDH and CK were found to be elevated to be a good marker of muscle damage and progression of diseases. CRP as a marker of inflammation was also found to be elevated. Enzymes like acid phosphatase increased abruptly while alkaline phosphatase was irregular. Liver enzymes SGOT and SGPT activity were also enhanced. Conclusion: Increased level of transaminases can be reflective of the formation of various amino acids for the synthesis of new protein and for channeling of glutamate and aspartate along with glycine for the synthesis of purine and pyrimidine nucleotides. Objective: The main objective of the present study is to correlate the effect of certain enzymes in diagnosis of dengue fever (DF) and impact of these elevated/decreased blood levels of enzymes on patients of DF. Methods: The study was carried out on 30 patients suspected to be suffering from DF. Blood sample was collected and tested for various parameters such as protein (albumin), lactate dehydrogenase (LDH), creatinine kinase (CK), C-reactive protein (CRP), acid phosphatase, alkaline phosphatase, serum glutamic oxaloacetic transaminase (SGOT), and serum glutamic pyruvic transaminase (SGPT). Results: Serum enzymes such as LDH and CK were found to be elevated to be a good marker of muscle damage and progression of diseases. CRP as a marker of inflammation was also found to be elevated. Enzymes like acid phosphatase increased abruptly while alkaline phosphatase was irregular. Liver enzymes SGOT and SGPT activity were also enhanced. Conclusion: Increased level of transaminases can be reflective of the formation of various amino acids for the synthesis of new protein and for channeling of glutamate and aspartate along with glycine for the synthesis of purine and pyrimidine nucleotides.